Changes in oral health-related quality of life during implant treatment in partially edentulous patients: A prospective study. Issue 4 (October 2016) - Yoshida, Tadashi; Masaki, Chihiro; Komai, Hideki; Misumi, Saori; Mukaibo, Taro; Kondo, Yusuke; Nakamoto, Tetsuji; Hosokawa, Ryuji
Abstract: Purpose: The aim of this prospective study was to evaluate the changes in oral health-related quality of life (OHRQoL) during implant treatment for partially edentulous patients, and to evaluate the influence of the type of partially edentulous arch. Methods: Twenty patients with a small number of lost teeth (fewer than 4 teeth) who underwent implant treatment were selected. Chronological QOL change during implant treatment was measured. The subjects completed the shortened Japanese version of the Oral Health Impact Profile (OHIP-J14) before the surgery (T0), 1 week after the surgery (T1), 1 week after interim prosthesis placement (T2), and 1 week after definitive prosthesis placement (T3). Complete data of the twenty subjects were analyzed with the Wilcoxon signed-rank test. Results: The total OHIP-J14 score was significantly reduced only at T3 ( P  < 0.05). "Physical pain" and "Physical disability" scores significantly decreased at T3, and "Psychological discomfort" scores also significantly dropped at T2. However, "Functional limitation" scores significantly increased at T1. "Psychological disability", "Social disability", and "Handicap" scores remained the same. On the other hand, in the comparison depending on the type of partially edentulous arch, the total OHIP-J14 score significantly decreased at T3 in the unilateral free-end edentulous space, whereas no significant difference was observed in the bounded edentulous space. Conclusion: Although there is a temporary functional limitation after implant placement in overall OHRQoL improvement was observed after the definitive prosthesis placement. Moreover, implant treatment was more effective in the unilateral free-end edentulous space.